2020
DOI: 10.3389/fimmu.2020.00946
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Landscape of Autoimmune Hemolytic Anemia

Abstract: Autoimmune hemolytic anemia (AIHA) is a greatly heterogeneous disease due to autoantibodies directed against erythrocytes, with or without complement activation. The clinical picture ranges from mild/compensated to life-threatening anemia, depending on the antibody's thermal amplitude, isotype and ability to fix complement, as well as on bone marrow compensation. Since few years ago, steroids, immunesuppressants and splenectomy have been the mainstay of treatment. More recently, several target therapies are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
107
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(122 citation statements)
references
References 42 publications
3
107
0
12
Order By: Relevance
“…It has been shown that a human immunodeficiency virus (HIV) infection may induce production of autoantibodies, owing to molecular mimicry [47]. Moreover, HIV infection is an independent risk factor for AIHA and increases the incidence of AIHA more than 20-fold [8,48]. In the case of HIV infection, as well as in other immunodeficiencies (e.g.…”
Section: Pathogenesis Of Aihamentioning
confidence: 99%
“…It has been shown that a human immunodeficiency virus (HIV) infection may induce production of autoantibodies, owing to molecular mimicry [47]. Moreover, HIV infection is an independent risk factor for AIHA and increases the incidence of AIHA more than 20-fold [8,48]. In the case of HIV infection, as well as in other immunodeficiencies (e.g.…”
Section: Pathogenesis Of Aihamentioning
confidence: 99%
“…In those cases, the autoantibodies may be detected by enhanced DAT assays utilizing reagents such as anti-IgA and anti-IgM to achieve agglutination of such antibody-coated erythrocytes or by flow cytometry. IgG autoantibodies may bind to the RBCs at a relatively low level, causing hemolysis, but being below the threshold of detection for the commonly performed DAT, while flow cytometry is more sensitive to detect these low levels of antibodies bound to RBCs [ 12 ].…”
Section: Warm Antibody Aiha (W-aiha)mentioning
confidence: 99%
“…Most of COVID-related cytopenias described in literature developed at the time of COVID-19 infection (generally within the first month). It is largely known that autoimmune cytopenias may be triggered by viral and bacterial infections, due to mechanisms of molecular mimicry, neo-antigen generation and hidden epitope spreading ( 47 , 48 ). Interestingly, the RBC membrane protein ankyrin-1 was found to share a 100% identity with the SARS-CoV-2 surface glycoprotein Spike ( 49 ), suggesting a molecular mimicry mechanism for AIHA.…”
Section: Discussionmentioning
confidence: 99%